2019
DOI: 10.1038/s41440-018-0197-z
|View full text |Cite
|
Sign up to set email alerts
|

Newly manufactured Marukome MK-34-1 miso with angiotensin-converting enzyme inhibitory activity and its antihypertensive effects in genetic hypertensive rat models

Abstract: We newly manufactured miso rich in angiotensin-converting enzyme (ACE) inhibitory activity (Marukome MK-34-1, shinki miso) and investigated its antihypertensive properties in rat models of genetic hypertension. ACE inhibitory activity was tenfold higher in shinki miso than in commercially available Marukome Nenrin miso (nenrin miso). The inhibitory activity of shinki miso was confined to <3 kDa fractions and was detected in several fractions with high polarity by C 18 highperformance liquid chromatography. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Miso increases sodium excretion in the kidney and inhibits sodium reabsorption in the renal tubules. Nicotinamide extracted from soybeans inhibits ACE activity, and miso has the same effect [ 44 , 45 ]. Therefore, miso enhances sodium excretion, and people who consume it habitually might have been evaluated as having an excessive dietary salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…Miso increases sodium excretion in the kidney and inhibits sodium reabsorption in the renal tubules. Nicotinamide extracted from soybeans inhibits ACE activity, and miso has the same effect [ 44 , 45 ]. Therefore, miso enhances sodium excretion, and people who consume it habitually might have been evaluated as having an excessive dietary salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitory activity of casein miso paste was also higher than other miso pastes, which correlates with the higher concentration of antihypertensive peptides found in casein miso paste (Inoue et al, 2009). Tomari et al (2019) developed a new type of miso with improved ACE inhibitory activity called Marukome MK-34-1 miso (shinki miso). An in-vivo study reported that shinki miso exhibited higher antihypertensive effects in SHRSP compared to regular miso.…”
Section: Antihypertensive Effects Of Soybean Pastementioning
confidence: 96%
“…This study also revealed the natriuresis and diuresis through the dopamine system by habitual dietary intake of miso. In addition, the attenuation of the salt-induced blood pressure elevation observed in habitual dietary intake of miso soup was also demonstrated in stroke-prone SHR, which are also genetically salt-sensitive rats [ 33 ]. Miso intake was also confirmed to be associated with alleviation of organ damage and have protective effects against stroke [ 32 34 ].…”
Section: Miso Intake In Basic Studiesmentioning
confidence: 99%
“…Interestingly, fermented soybeans, including miso, are known to block the angiotensin-converting enzyme (ACE) activity [ 54 , 55 ]. The active ingredient of miso that has ACE inhibitory activity was reported to be a small peptide [ 33 ]. Therefore, such small peptides with anti-ACE inhibitory effects might work directly in several organs, including the brain.…”
Section: Effects Of Miso On Sympathetic Nerve Systemmentioning
confidence: 99%